1969
DOI: 10.1002/qj.49709540509
|View full text |Cite
|
Sign up to set email alerts
|

Modification of mean flow and turbulent energy by a change in surface roughness under conditions of neutral stability

Abstract: SUMMARYA theory is developed which describes the adjustment of the flow of a hydrostatically neutral fluid in the lower portion of a fully-turbulent boundary layer, after an abrupt change in surface roughness.The model is based on the hypothesis that the horizontal shear stress is proportional to the turbulent energy. The theory postulates that the flow is primarily governed by the dominant terms of the horizontalmomentum, continuity, and turbulent-energy equations. The model was solved by numerical techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
0
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 7 publications
7
77
0
1
Order By: Relevance
“…The upper level of the transition layer constitutes the top of the internal boundary layer. Floors et al (2011) found, from an analysis of measurements at Høvsøre, that the height of the internal boundary layer for momentum and wind velocity are different, in agreement with results from classical model simulations of the internal boundary layer, such as those of Rao et al (1974) and Peterson (1969). It was found that the flow at Høvsøre was in full equilibrium with the land surface below 15 m; followed by a transition layer in which the wind velocity conforms to that over the sea; the top of this layer is at ≈80 m and above this the marine wind profile prevails although the momentum is still in a transition phase between sea and land conditions.…”
Section: Reversal-height Analysissupporting
confidence: 64%
“…The upper level of the transition layer constitutes the top of the internal boundary layer. Floors et al (2011) found, from an analysis of measurements at Høvsøre, that the height of the internal boundary layer for momentum and wind velocity are different, in agreement with results from classical model simulations of the internal boundary layer, such as those of Rao et al (1974) and Peterson (1969). It was found that the flow at Høvsøre was in full equilibrium with the land surface below 15 m; followed by a transition layer in which the wind velocity conforms to that over the sea; the top of this layer is at ≈80 m and above this the marine wind profile prevails although the momentum is still in a transition phase between sea and land conditions.…”
Section: Reversal-height Analysissupporting
confidence: 64%
“…3, Bognaes mast), that wind profiles above and below h are approximately logarithmic. More accurate theoretical models (e.g., Peterson, 1969) show, however, that this picture is only approximately correct.…”
Section: Data Basementioning
confidence: 99%
“…Therefore, Peterson et al (1979) also studied the profiles at another site, Bognaes, where the slope was negligible. We have also used some of the Bognaes results.…”
Section: Data Basementioning
confidence: 99%
See 1 more Smart Citation
“…When one roughness regime gives way to another, the flow near the ground gradually adjusts to the new surface characteristics. This process is often represented mathematically by local internal boundary layers (IBLs), which grow vertically downstream of a roughness boundary (Elliott 1958;Panofsky and Townsend 1964;Townsend 1965;Peterson 1969;Blom and Wartena 1969).…”
Section: Introductionmentioning
confidence: 99%